KNOWLEDGE MANAGEMENT’S ROLE IN ORGANIZATION MATURITY IN PROJECT MANAGEMENT - Smith, Dedrick A.; Hannon, John (International Journal of Research -GRANTHAALAYAH, 2015)
In this paper, we review knowledge management’s role in project management (PM). The authors speculate that knowledge management is an indicator of organizational maturity project management. This is as an organization increases its maturity in PM, it uses both informal and formal channels for knowledge transfers between the firm’s actors. The researchers used an online survey and telephone interview process to collect data. The data showed that there was a positive relationship between knowledge management and organization maturity in project management. In immature firms, the project manager uses informal learning channels to increase their own tacit project management knowledge. For example, organizations useprojectmanagers’interactions, (internally and externally),unofficialexternaltrainingcourses,andprofessionalorganizationstoincreaseorganizationallearning.As organizational maturityincreases,managersbegintocodifythesechannelsintoformalones thereby creatingexplicit knowledge. They use channels like databaserepositories,manuals,websites,and official internalandexternaltrainingopportunitiesto foster organizational learning. In addition, firms use other artifacts suchas PM guides and manuals to facilitate education and knowledge transfer in an organization’s PM methodology and toolsets. The study also sets forth specific recommendations to project managers, organizations, and the Project Management Institute to include knowledge management and organizational learning as indicators of organization maturity in their Organizational Project Management Maturity Model (OPM3©) model.